Feasibility study of teachers contributions in curriculum processes in Iranian Education System - Kourosh FathiVājargāh (فصلنامه نوآوری‌های آموزشی, 2004)
Realistic curriculum planning for schools requires the contribution of all groups, especially teachers, who influence the process of decision making in education. Since teachers have valuable experiences about school activities and are aware of the students needs and problems, they should be considered as the main important element of decision making on curriculum planning. This research has tried to show the extent, and the possibility, of teachers contribution in curriculum planning in Iran and have investigated the results of such contribution as well. A researcher-made questionnaire has been used to collect data from a sample of high school teachers in Tehran and experts of curriculum planning of the Ministry of Education concerning the extent of teachers contribution in curriculum planning, the factors which facilitate this contribution, and the positive and negative effects of it.